"The Doctor Says You Cannot Have [Buprenorphine]" Autonomy and Use of Prescribed or Non-Prescribed Buprenorphine. (27th May 2021) - Hayes, Benjamin T.; Jakubowski, Andrea; Fitzsimmons, Christine; Garcia, Billy; Ramirez, Franklin; Fox, Aaron D.
Abstract: Background: People may overcome barriers to professional buprenorphine treatment by using non-prescribed buprenorphine (NPB) to manage opioid use disorder (OUD). Little is known about how people perceive NPB differently than formal treatment. This qualitative study investigated how and why people use NPB as an alternative to formal treatment. Methods: In-depth, semi-structured interviews were conducted with participants of harm reduction agencies ( N   =  22) who had used buprenorphine. Investigators independently coded transcribed interviews, generating themes through iterative reading and analysis of transcripts. Results: Three main factors drove decisions about prescribed and non-prescribed buprenorphine use: 1) autonomy; 2) treatment goals; and 3) negative early experiences with NPB. An overarching theme from our analysis was that participants valued autonomy in seeking to control their substance use. NPB was a valuable tool toward this goal and professional OUD treatment could impede autonomy. Participants mostly used NPB to "self-manage" OUD symptoms. Many participants had concerns about long-term buprenorphine treatment and instead used NPB over short periods of time. Several participants also reported negative experiences with NPB, including symptoms of withdrawal, which then deterred them from seeking out professional treatment. Conclusions: These results support prior studies showing that people use NPB to self-manage withdrawal symptoms and to reduce use of illicit opioids. Despite these benefits, participants focused on short-term goals and negative consequences were common. Increasing buprenorphine treatment engagement may require attention to patients' sense of autonomy, and also assurance that long-term treatment is safe, effective, and reliably accessible.